ChatGPT: examining language lecturers' perspectives on its integration in teaching and learning / Salwa Othman ... [et al.] - Othman, Salwa; Nik Ismail Azlan, Nik Mastura; Mohamad Shah, Dianna Suzieanna; Mohandas, Eliyas Sulaiman; Azhari, Muhammad Aizat (Universiti Teknologi MARA, Kedah, 2024)
In higher education, ChatGPT has proven useful for several reasons: 1) it provides access to a wealth of information for practicing language skills in a natural and interactive way, 2) it provides personalised learning and guidance for learners and 3) it provides the ability to translate from one language to another, offering a new and innovative way to learn a new language. This paper aims to examine language lecturers' perceptions of ChatGPT and its integration into teaching and learning in Malaysia through a series of interview questions using the Technology Acceptance Model (TAM), specifically Perceived Usefulness (PU) and Perceived Ease of Use (PEU). The qualitative study conducted semi-structured interviews based on the model with 16 university language lecturers from a public university in Selangor, Malaysia. Participants were chosen based on their familiarity with ChatGPT for teaching and learning purposes. The transcribed findings reveal that language lecturers would readily embrace ChatGPT, but were concerned about the excessive reliance on ChatGPT, which could lead to students’ deterioration in their critical thinking and problem-solving capabilities. The results highlight the importance of recognizing the potential advantages of employing ChatGPT technology within higher education environments.